Age But Not Sex Is Associated With Efficacy and Adverse Events Following Administration of Intravenous Migraine Medication: An Analysis of a Clinical Trial Database. Issue 10 (21st October 2015) - Friedman, Benjamin W.; Cisewski, David H.; Holden, Lynne; Bijur, Polly E.; Gallagher, E. John
Abstract : Background: Migraine prevalence is associated with both sex and age. Differences in efficacy of parenteral migraine medication administration based on the sex and age of the patient have not been explored in the published literature. Objective: The objective was to determine whether sex and age are associated with short‐term headache relief, sustained headache freedom, or adverse medication effects in data collected during 3 emergency department (ED)‐based acute migraine comparative efficacy trials. Methods: Data were combined from 3 studies in which patients who presented to an ED with acute migraine were randomized to one of the following intravenous medication regimens: (1) metoclopramide combined with diphenhydramine; (2) metoclopramide combined with diphenhydramine and dexamethasone; (3) metoclopramide alone; (4) ketorolac; or (5) valproate. In each of these studies, (1) short‐term efficacy (patient description of the headache as "mild" or "none" 1 hour after medication administration); (2) sustained efficacy (patient description of the headache as "none" within 2 hours of medication administration and no headache recurrence for 24 hours post ED discharge); and (3) the frequency of any adverse medication effects within 24 hours of medication administration was determined. For each of the medication regimens studied, efficacy and adverse event rates were compared between men vs women and the older vs the younger half of patients. Multivariate logistic regression models were constructed in which sex and age were maintained in the model as well as variables representing each of the medication regimens patients received. Results: A total of 884 patients were included in this analysis (140 men and 744 women). The median age was 35 years. After controlling for age and medication received, female sex was not associated with short‐term efficacy (OR 0.98 [95% confidence interval (CI): 0.66, 1.46]), sustained efficacy (OR 0.72 [95%CI: 0.45, 1.15]), or adverse events (OR 1.14 [95%CI: 0.77, 1.71]). Age >36 years, however, was associated with short‐term efficacy (OR 0.66 [95%CI: 0.49, 0.88]), sustained efficacy (OR 0.50 [95%CI: 0.34, 0.73]), and adverse events (OR 1.36 [95%CI: 1.02, 1.82]). Conclusion: Sex was not associated with response to parenteral acute migraine medication. Age was associated with both efficacy and adverse events.